SURVEY MANAJEMEN SARANA DAN PRASARANA OLAHRAGA DALAM RANGKA PERSIAPAN PON XXI ACEH – SUMUT 2024 - Yulinar, Yulinar; Musran, Musran; Rahman, Auva Fadhlur; Husaini, Husaini (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This study examines the management of sports facilities and infrastructure in preparation for PON XXI Aceh-Sumut 2024. The purpose of the study was to determine the planning, organizing, actuating, controlling in the implementation of PON XXI Aceh-Sumut 2024 Sports activities. Qualitative research method, research respondents are people related to the implementation of PON XXI Aceh-Sumut 2024 activities. Data collection techniques by interview, observation and documentation. Data analysis using data triangulation. Based on the results of the study, it can be explained that planning has been prepared since the determination of the host for the implementation of PON XXI Aceh-Sumut 2024. Procurement of facilities and infrastructure has been planned according to the sports branches determined in Aceh Province. Organization is based on matters concerning common interests and provisions for placement of places based on previous matters. The facilities and infrastructure provided are in accordance with the needs determined for each sport being fostered. Actuation is carried out comprehensively based on the results of control in the field. Supervision (controlling) of the supervision process is also carried out well so that it will run smoothly as expected